Handbook of residual stress and deformation of steel - Totten, George E.; Howes, Maurice A. H.; Inoue, Tatsuo, 1939- (ASM International, 2002)
Annotation Examines the factors that contribute to overall steel deformation problems. The 27 articles address the effect of materials and processing, the measurement and prediction of residual stress and distortion, and residual stress formation in the shaping of materials, during hardening processes, and during manufacturing processes. Some of the topics are the stability and relaxation behavior of macro and micro residual stresses, stress determination in coatings, the effects of process equipment design, the application of metallo- thermo-mechanic to quenching, inducing compressive stresses through controlled shot peening, and the origin and assessment of residual stresses during welding and brazing. Annotation c. Book News, Inc., Portland, OR (booknews.com)
Keywords: Steel -- Fatigue -- Handbooks, manuals, etc.; Residual stresses -- Handbooks, manuals, etc.; elektronické knihy; electronic books